Spore Production of Biocontrol Agent Trichoderma Harzianum: Effect of C/N ratio and Glucose Concentration - Said, Syahiddin Dahlan (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2007)
Effects of medium condition on spore production and spore viability of Trichoderma harzianum UPM 29 isolated from oil palm rhizosphere were studied. The carbon to nitrogen (CN) ratio and glucose concentration have significant effect on spore production and spore viability of the fungus. Highest spore production (1.6x108spores/ml) was obtained in a medium containing 30 g/l glucose with a CN ratio of 24. The highest spore viability (52.5%) was produced in the culture grown on media with glucose concentration of 30 g/l and with a C/N ratio of 44.Keywords: biocontrol agent, biofungicide, spore viability, Trichoderma harzianum